IoT-Based Package Drop Box System Using Arduino Uno and ESP32-CAM - Simatupang, Frengki; Sigiro, Marojahan M.T; Sinambela, Eka Stephani; Manalu, Istas Pratomo (Jurnal Sistem Cerdas, 2025)
The rapid growth of e-commerce activity in Indonesia has led to a surge in package delivery volumes, resulting in increased workloads for couriers and a higher risk of delivery failures when recipients are not present at the delivery location. This issue demands an innovative solution that can address logistical challenges in an automated, secure, and efficient manner. This study aims to design and implement an IoT-Based Package Drop Box system that integrates Arduino Uno, Wemos D1 Mini, ESP32-CAM, and the GM66 barcode scanner, along with a web interface and WhatsApp notification service. The methodology follows a prototype engineering approach consisting of need analysis, system design, implementation, and hardware-software testing phases. The test results demonstrate that the system can successfully verify package tracking numbers via barcode scanning at an optimal distance of 10–19 cm, automatically unlock the box, capture images inside the drop box using ESP32-CAM, and send real-time delivery notifications to users via WhatsApp. The system is also capable of storing data locally when the internet connection is lost and synchronizing it once the connection is restored. The findings conclude that the integrated system provides a practical and reliable solution to common delivery issues and has the potential to be further developed for smart home environments or broader Internet of Things-based logistics systems.